Surface analysis and techniques in biology - Smentkowski, Vincent S. (Springer International Publishing, 2014)
The outer layer of bulk solid or liquid samples is referred to as the surface of the sample/material.  At the surface, the composition, microstructure, phase, chemical bonding, electronic states, and/or texture is often different than that of the bulk material. The outer surface is where many material interactions/reactions take place. This is especially true biomaterials which may be fabricated into bio-devices and in turn implanted into tissues and organs.  Surfaces of biomaterials (synthetic or modified natural materials) are of critical importance since the surface is typically the only part of the biomaterial/bio-device that comes in contact with the biological system.   Analytical techniques are required to characterize the surface of biomaterials and quantify their impact in real-world biological systems.  Surface analysis of biological materials started in the 1960's and the number of researchers working in this area have increased very rapidly since then, a number of advances have been made to standard surface analytical instrumentation, and a number of new instruments have been introduced.   We felt the time was right for a book which summarized the main surface analysis techniques that are being used to study biological specimens/systems. The compilation of chapters in this book will help the biological research community realize the benefits that surface analysis provides.  We look forward to seeing a larger number of biologists and medical specialists using the techniques discussed in this book. It is of importance to note that new analysis instruments are continuously being developed and introduced to the scientific community - we look forward to seeing what the future has in store.  We are also excited to see next generation medical devices, which will benefit from surface analysis, and which will help our society. About the Editor Vincent S. Smentkowski is a Senior Scientist in the Nanostructures and Surfaces Laboratory at General Electric Global Research (GEGR) where he performs surface analysis to support research programs at GEGR, GE businesses, and strategic partners. Currently, his research is focused on the applications of ToF-SIMS analysis, emphasizing how multivariate statistical analysis tools facilitate data reduction. Vin holds 6 U.S. patents, more than 85 publications in referred journals, greater than 100 GEGR internal manuscripts, has co-authored 3 book chapters, and has presented numerous contributed and invited talks. Vin is a Fellow of the American Vacuum Society.